The The Decline of Democracy and Indications of Authoritarianism: A Study of the Dynamics of Contemporary Indonesian Politics: A Study of the Dynamics of Contemporary Indonesian Politics - Azka, Hakim Muttaqie (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2026)
This study examines the phenomenon of democracy in Indonesia after the 1998 reforms, which was marked by a weakening of the substantive quality of democracy and the strengthening of covert authoritarianism. Using a qualitative approach and desk study methods, this study analyzes the dynamics of contemporary Indonesian politics through Robert A. Dahl's theory of polyarchy, Larry Diamond's concept of democratic consolidation, and Andreas Schedler and Nancy Bermeo's framework of electoral authoritarianism. The findings indicate that although democratic procedures, such as elections, remain formally valid, the practices of power tend to be exclusive, repressive, and manipulative. Civic space has been narrowed, criticism of power has been criminalized, and independent oversight institutions have lost their function. This phenomenon indicates a shift toward a hybrid regime, or a formal democracy but authoritarian in substance. To prevent anti-democratic consolidation of power, institutional reform, the enforcement of a just rule of law, and the empowerment of civil society as a countervailing force are necessary. This research is expected to contribute to the academic literature on latent threats to democracy and provide a normative basis for strengthening substantive democracy in Indonesia.